Resilience of Dutch probation officers: A critical need for a critical profession. (August 2014) - Vogelvang, Bas; Clarke, Jo; Sperna Weiland, Aleid; Vosters, Nanne; Button, Lori
This article presents the first research findings into the resilience of Dutch probation officers. The research has been a part of European-funded SPORE project, that aimed to identify approaches that appear to have a positive impact on probation officers' resilience. The theoretical starting point for the research was the Stress Shield Model, developed and validated in research among police officers. This model views resilience as the capacity to cope with, adapt to, and develop from the demands, challenges and changes encountered as a result of working in a critical occupation. The model describes resilience as an outcome, resulting from the interaction between organizational, peer related, and individual factors. By means of five focus groups and an internet survey consisting of questionnaires measuring the model factors, the research aimed to identify how the factors in the model influence the resilience of Dutch probation officers (POs), what effective or promising practices exist in the Netherlands for the purpose of strengthening resilience of POs, what supporting activities can be carried out by the management, and finally what recommendations can be made for developments at a national and European level. The survey was completed by 165 POs. Results indicate that for Dutch POs it is not primarily clients who have a negative impact on their resilience. Worker resilience appears to be primarily threatened, but also developed and strengthened, by characteristics of the organization and team, as well as the characteristics of the individual worker himself. As an organization, the Dutch Probation Service appears to effectively build and sustain probation officers' sense of empowerment, which prepares them for future stress. In addition, the research shows the importance of a resilient team and of an organization that provides teams with proper support. Based on these research findings, a set of detailed recommendations is presented that has now been adopted by the management of the Dutch Probation Service.